Quaternion Stieltjes Transform and Quaternion Laplace-Stieltjes Transform - Parmar, Khinal; Gorty, V. R. Lakshmi (Communications in Mathematics and Applications, 2021)
In this study, we introduce quaternion Stieltjes transform. Various properties of the quaternion Stieltjes transform are derived. We also define quaternion Laplace-Stieltjes transform and operational properties of quaternion Laplace-Stieltjes transform are established. The theory is supported with applications in mathematical physics.
Keywords: Quaternion Stieltjes transform; Quaternion Laplace-Stieltjes transform; Convolution theorem; Applications